Identification of a novel sequence that governs both polyadenylation and alternative splicing in region E3 of adenovirus. - Brady, H A (1987)
Region E3 encodes four major overlapping mRNAs with different splicing patterns. There are two poly(A) sites, an upstream site called E3A and a downstream site called E3B. We have analyzed virus mutants with deletions or insertions in E3 in order to identify sequences that function in the alternative processing of E3 pre-mRNAs, and to understand what determines which poly(A) sites and which splice sites are used. In previous studies we established that the 5' boundary of the E3A poly(A) signal is at an ATTAAA sequence. We now show, using viable virus mutants, that the 3' boundary of the E3A signal is located within 47-62 nucleotides (nt) downstream of the ATTAAA (17-32 nt downstream of the last microheterogenous poly(A) addition site). Our data further suggest that the spacing between the ATTAAA, the cleavage sites, and the essential downstream sequences may be important in E3A 3' end formation. Of particular interest, these mutants suggest a novel mechanism for the control of alternative pre-mRNA processing. Mutants which are almost completely defective in E3A 3' end formation display greatly increased use of a 3' splice site located 4 nt upstream of the ATTAAA. The mRNA that uses this 3' splice site is polyadenylated at the E3B poly(A) site. We suggest, for this particular case, that alternative pre-mRNA processing could be determined by a competition between trans-acting factors that function in E3A 3' end formation or in splicing. These factors could compete for overlapping sequences in pre-mRNA.